Nanotechnology: Review of concepts and potential application of sensing platforms in food safety. (October 2018) - Krishna, Venkatramana D.; Wu, Kai; Su, Diqing; Cheeran, Maxim C.J.; Wang, Jian-Ping; Perez, Andres
Abstract: In recent years a number of new nanotechnology based platforms have been developed for detection of wide variety of targets including infectious agents, protein biomarkers, nucleic acids, drugs, and cancer cells. Nanomaterials such as magnetic nanoparticles, quantum dots, carbon nanotubes, nanowires, and nanosensors like giant magnetoresistance (GMR) sensors are used to quantitatively detect biomolecules with, experimentally, relatively good accuracy. There has been a growing interest in the use of magnetic fields in biosensing applications. Because biological samples have no ferromagnetic property and therefore there is no interference with complex sample matrix, detection of infectious agents from minimally processed samples is possible. Here, we provide a brief overview of the recent emergence of nanotechnology-based techniques for the detection and monitoring of foodborne diseases. In addition, the potential applications and future perspectives of nanotechnology on food safety are discussed. Ultimately, the review is expected to stimulate and provide directions to the development and application of nanotechnology-based tests for the early detection, and eventual control of foodborne diseases. Highlights: Nanotechnology platforms have been developed for detection of variety of targets. We reviewed nanotechnology for the detection and monitoring of foodborne diseases. Discussed the potential applications of nanotechnology on food safety.